2004
DOI: 10.1007/978-3-540-44419-0_22
|View full text |Cite
|
Sign up to set email alerts
|

Computational Simulation of a Heavy Vehicle Trailer Wake

Abstract: To better understand the flow mechanisms that contribute to the aerodynamic drag of heavy vehicles, unsteady large-eddy simulations are performed to model the wake of a truncated trailer geometry above a no-slip surface. The truncation of the heavy vehicle trailer is done to reduce the computational time needed to perform the simulations. Both unsteady and time-averaged results are presented from these simulations for two grids. A comparison of velocity fields with those obtained from a wind tunnel study demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 4 publications
(2 reference statements)
7
8
0
Order By: Relevance
“…However, when the PANS equations are used with CDS, the flow topology is anti-symmetric to the experiments -flow state II ( Fig. 4(f)), but similar to the results of the LES of Rao et al (2018b) and Ortega et al (2004), and to the recent experimental investigations of Schmidt et al…”
Section: β ¼ 0 ∘supporting
confidence: 84%
See 3 more Smart Citations
“…However, when the PANS equations are used with CDS, the flow topology is anti-symmetric to the experiments -flow state II ( Fig. 4(f)), but similar to the results of the LES of Rao et al (2018b) and Ortega et al (2004), and to the recent experimental investigations of Schmidt et al…”
Section: β ¼ 0 ∘supporting
confidence: 84%
“…Sitlani and Aung (2006) reported a 46% increase in the drag coefficient for a GTS model with a sharp lower frontal edge as compared to the standard case with the filleted edge. However, the flow topology at the rear of the model was found to be invariant of the frontal shape of the model as seen in the results of Ortega et al (2004), where an asymmetrical flow topology similar to Storms et al (2001) was observed in the wake of a truncated GTS model, albeit transposed across the lateral midplane. The schematic of the GTS model used in this study is shown in Fig.…”
Section: Problem Setupsupporting
confidence: 59%
See 2 more Smart Citations
“…To accurately predict the integrated forces over the GTS is particularly important to be able to model the unsteady flow behavior, vortex shedding frequency, and to obtain an accurate prediction of boundary layer separation. Various studies have been taking place using RANS, 7,8 Large Eddy Simulations (LES), 9 and hybrid RANS/LES methods. 10 Due to the complexity of the problem, LES has been shown to be the most reliable method when it comes to the predictions of the flow features and integrated forces.…”
Section: Introductionmentioning
confidence: 99%